Enhancing Morphological and Physiological Sugarcane Growth through Natural Plant Growth Regulators Made of Banana Weevil - Saktiyono Sigit Tri Pamungkas; Karisma Ridha Yulianto; Fitria Nugraheni Sukmawati; Yudhi Pramudya; Farrah Fadhillah Hanum; Muhammad Sahbudin; Sukarji Sukarji (The University of Lampung, 2026)
Natural plant growth regulators (NPGR) have a significant impact on plant growth, particularly on plant morphological and physiological characteristics. The aim of this study was to examine the effects of immersion duration with banana weevil NPGR on the physiological and morphological traits of bud chips of sugarcane clone PS 862. The experiment was arranged in a randomized completed block design with a single factor of immersion duration. Five immersion treatments included T0 (control), T1 (1.5 h), T2 (3 h), T3 (4.5 h), and T4 (6 h), were performed with 5 samples and 3 blocks of replications, resulting in a total of 75 plant samples. Results revealed that immersion of 1.5 h was optimal for NPGR absorption in sugarcane seedlings with better plant growth. Immersion for 1.5 h resulted in the significantly highest stem diameter (6.03 mm), the longest root length (43.73 cm), and the highest stomatal density (127.04 stomata/mm²). These indicated the improved physiological performance of sugarcane seedlings under moderate NPGR exposure. Significant effect was not observed on the total amount of chlorophyll; most likely due to the small number of leaves generated during the seedling phase. The study concluded that using NPGR, especially with a 1.5 h immersion time, could improve the growth and morphological characteristics of BC variety PS 862.